2016
DOI: 10.7150/jca.16609
|View full text |Cite
|
Sign up to set email alerts
|

Association of common variants in MTAP with susceptibility and overall survival of osteosarcoma: a two-stage population-based study in Han Chinese

Abstract: Osteosarcoma (OS) is a common malignant tumor, which exists widely in the bone of children and adolescents, and genetic factors may influence its susceptibility. Recently, the gene MTAP has been reported to be associated with OS in a Caucasian population. To investigate the association of common variants in MTAP with OS risk in Han Chinese individuals, we designed a two-stage case-control study with 392 OS patients and 1,578 unrelated healthy controls of Han Chinese individuals. A total of 17 tagging single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, studies have shown that germline mutations in MTAP result in an autosomal-dominant bone cancer syndrome, and that MTAP knockout, independent of CDKN2A deletion, promotes lymphoma in mice (3)(4)(5). MTAP deficiency has also been independently associated with poor clinical outcomes in patients of several cancer types (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that germline mutations in MTAP result in an autosomal-dominant bone cancer syndrome, and that MTAP knockout, independent of CDKN2A deletion, promotes lymphoma in mice (3)(4)(5). MTAP deficiency has also been independently associated with poor clinical outcomes in patients of several cancer types (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Our metaanalysis also presented strong evidence that MTAP rs7023329 (under allelic and dominant model) and rs7027989 (under the allelic model) were associated with a lower risk of OS in Asians. Although the exact mechanism of SNP rs7023329 affect OS risk remains unknown, Zhi et al hypothesized that SNP rs7023329 might coexist in linkage disequilibrium with one certain variants and affect its regulation machinery to associate with OS risk (42). The protein kinase C gamma (PRKCG) gene is located on chromosome 19q13.42 and functions as the major receptor for tumor promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of SNP rs7023329 affect OS risk remains unknown, Zhi et al. hypothesized that SNP rs7023329 might coexist in linkage disequilibrium with one certain variants and affect its regulation machinery to associate with OS risk ( 42 ). The protein kinase C gamma ( PRKCG ) gene is located on chromosome 19q13.42 and functions as the major receptor for tumor promoters.…”
Section: Discussionmentioning
confidence: 99%
“…We carefully designed our ANRIL modification experiments to only target ANRIL and showed that there were no significant gene expression changes in three neighboring protein-coding genes. Previously, one of these nearby protein-coding genes ( MTAP ) was identified in osteosarcoma [ 62 ]. It is thought to play a role in cancer cell etiology given its behavior as a tumor suppressor [ 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, one of these nearby protein-coding genes ( MTAP ) was identified in osteosarcoma [ 62 ]. It is thought to play a role in cancer cell etiology given its behavior as a tumor suppressor [ 62 , 63 , 64 , 65 ]. However, correlation analyses between the expression of MTAP and cisplatin and doxorubicin sensitivity found no relationship between them.…”
Section: Discussionmentioning
confidence: 99%